Analisis Peran Mikroorganisme Tanah Dalam Meningkatkan Kapasitas Infiltrasi - Hulu, Stefani Angel Kristin; Mendrofa, Trisna Sari (Jurnal Ilmu Pertanian dan Perikanan, 2024)
Soil infiltration capacity is a critical factor in water management and soil conservation, particularly in agricultural systems and natural ecosystems. Effective infiltration allows water to penetrate the soil, reducing surface runoff, preventing erosion, and enhancing groundwater reserves. A key element influencing infiltration capacity is the presence and activity of soil microorganisms, which play a vital role in soil structure formation and aggregate stability. This study aims to analyze the role of soil microorganisms, including bacteria, fungi, and actinobacteria, in enhancing infiltration capacity through organic matter decomposition, aggregate formation, and the production of exopolysaccharides that bind soil particles. The findings demonstrate that soils with active microbial populations exhibit significantly higher infiltration capacity compared to soils with limited microbial activity. This is attributed to microbial processes that improve soil structure, increase porosity, and stabilize aggregates, facilitating water absorption. The study underscores the importance of sustainable agricultural practices that support microbial diversity to improve soil quality and ecosystem resilience. By highlighting the essential contributions of soil microorganisms to infiltration, this research provides insights into soil health management strategies that enhance water retention and soil conservation.